Impact of Changes in Teaching Methods During the COVID-19 Pandemic: The Effect of Integrative E-Learning on Readiness for Change and Interest in Learning Among Indonesian University Students - Prasetyo, Anggun Resdasari; Nurtjahjanti, Harlina; Ardhiani, Lusi Nur (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
The COVID-19 pandemic has forced universities to conduct online learning, requiring lecturers to create innovative e-learning methods and students to be ready to adapt and show high interest in learning. This study aimed to examine the effect of an integrative e-learning method on students’ readiness and interest in learning at Universitas Diponegoro, Indonesia. This research was experimental, designed with one group pretest and posttest, and no control group. As many as 190 students participated, selected using clustered random sampling. Two measurement scales were used: the readiness for change scale and the interest in learning scale. The statistical analysis technique used was a paired sample t-test. The results of paired sample t-test analysis on readiness for change (p = 0.000; p < 0.05) and interest in learning (p = 0.000; p < 0.05) showed significant differences between the pretest and posttest data. The findings indicated that students who participate in integrative e-learning show significant change in the level of readiness and interest in learning.